ABOUT THE GUARANTEED INTRADEPARTMENTAL RESERVE IN THE CONTEXT OF INTRALOGISTICS: ABOUT THE GUARANTEED INTRADEPARTMENTAL RESERVE IN THE CONTEXT OF INTRALOGISTICS - Stoyanov, Svetlozar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
In general, the current paper implies the conclusion that the determination of the impact of randomly occurring pauses in the work of the production unit with continuous technological process depends on the created intradepartmental guaranteed reserve.